Evaluation of Kubota tractor performance and cost: case study in Tradewinds Plantations Berhad, Ulu Papan Estates, Kota Tinggi, Johor / Mohamad Fikri Zaki and Muhammad Aliuddin - Zaki, Mohamad Fikri; Aliuddin, Muhammad (Faculty of Plantation and Agrotechnology, 2018)
Malaysia and Indonesia now stands as two biggest productions of oil palm in the world productions. Tractor number are growth rapidly in Malaysia and the tractor size increase and more efficient. Farm tractor widely in every farm and they also represent a total machinery costs. The main problems in this case study is frequently the maintenance problem in the plantations estates and record the total fixed cost and operations are not completed. A case study to determine the performance and cost of tractor for transporting FFB. The study was conducted in Ulu Papan Estates, Kota Tinggi. Johor. A primary data was collected to get the actual motion study which is measure time, distance and speed for tractor Kubota M9540 DT. The result was show for the TFC is 7.75 Tones per hour, EFC is 3.75 Tones per hour and FE is 48.3.9%. Secondary data was used to get the total cost and specification for the tractor. The yield and area cover is depends on the ability of the machine and skills of worker conducting the machines. The total cost per hectare for tractor Kubota M9540 DT is RM 66.77 (2013). RM 67.84 (2014), RM68.01 (2015). RM 66.73 (2016.) and RM 69.75 (2017). However the cost can be covered by tractor if more working hour and cover wide area.